Fiscal Monitor, October 2017 : Tackling Inequality. (Fiscal Monitor; Fiscal Monitor ;, 2017)
At the global level, inequality has declined substantially over the past three decades, but within national boundaries, the picture is mixed: some countries have experienced a reduction in inequality while others, particularly advanced economies, have seen a significant increase that has, among other things, contributed to growing public backlash against globalization. Excessive levels of inequality can erode social cohesion, lead to political polarization, and ultimately lower economic growth, but whether inequality is excessive depends on country-specific factors, including the growth context in which inequality arises, along with societal preferences. This Fiscal Monitor focuses on how fiscal policy can help governments address high levels of inequality while minimizing potential trade-offs between efficiency and equity. It documents recent trends in income inequality, including inequality both between and within countries, then examines the redistributive role of fiscal policies over recent decades and underscores the importance of appropriate design to minimize any efficiency costs. It then focuses on some key components of fiscal redistribution: progressivity of income taxation, universal basic income, and public spending policies for achieving more equitable education and health outcomes. The analysis relies on the existing theoretical and empirical literature, IMF work on inequality and fiscal policy, country experiences, and new analytical work, including various static microsimulation analyses based on household survey data. Simulations using a dynamic general equilibrium model calibrated to country-specific data and behavioral parameters illustrate the potential impact of alternative budget-neutral tax and transfer measures on income inequality and economic growth.